Foreign policy of A.M. López Obrador: Declarations and reality - V. L. Jeifets (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2021)
The paper examines the foreign policy of Mexico during the ﬁrst years of President A. M. López Obrador (AMLO) administration (2018‒2020). The research aims to both identify the key priorities of the country’s foreign policy (i.e., relations with the United States and Latin American countries, particularly in the context of the Venezuelan and Bolivian crises, as well as the Central American migration crisis) and to weigh it up against traditional patterns of Mexico’s foreign policy behavior, as well as to assess its overall feasibility. The latter issue is all the more relevant since the center-left administration of AMLO is constantly criticized for its ‘populism’. The paper shows that Mexico continues to prioritize relations with the United States not only in terms of economic cooperation (within the USMCA framework) and in addressing the migration crisis but also in terms of the overall foreign policy agenda setting as well. However, the author emphasizes that although the pressure from the United States is signiﬁcant and can take various forms, Mexico manages to pursue an independent and multifaceted policy, as the Venezuelan and Bolivian crises have shown. Such a policy is based on the traditional principles that have crystallized during the years of maneuvering between the interests of the great powers and which, according to AMLO and the Mexican Ministry of Foreign Aﬀairs, should not be subject to any revision. These principles include non-interference in the internal aﬀairs of other states and respect for their sovereignty, as well as respect for the right to political asylum. It is these principles that may contribute to reinforcing the international role of Mexico both regionally and globally despite a rather limited involvement of the current administration in foreign policy matters and its focus on domestic issues. Thus, the author concludes that beneath the populist rhetoric of A. M. López Obrador lies a fairly traditional foreign policy, warranted by the domestic situation and international environment.